Recording Postprandial Glucose Reactions with Potato Starch Structural Improvements - Sadaf Bashir; Zubair Farooq; Sobia Zafar; Tabussam Tufail; Huma Bader Ul Ain; Muzzamal Hussain; Entessar Al Jbawi; Purabi Saha; Roshan Kumar; Richard Owusu Nyarko (International Journal of Food Science)
The current study is aimed at modifying the structural makeup of potato starch through the application of heat and moisture to better control the postprandial glycemic response. Heat-moisture treatment (HMT) was used to prepare potato starch using different moisture levels and temperatures. The samples were digested with pancreatin to determine the % of easily digestible, slowly digestible, and resistant starch. Subjects were given pudding made with HMT potato starch, and their postprandial glycemic response was tracked by measuring their blood glucose levels. In addition, incremental and total incremental areas under the curve (IAUC, TIAUC) were also assessed. The current findings of in vitro enzymatic digestibility of potato starch showed inconsistent results as measured at different time intervals. Adding moisture and heating the mixture to 30 and 70°C both increased the amount of rapidly digestible starch in all of the treatments from 20 to 40%. The maximum value of slowly digestible starch was 43.63% when the sample was heated to 30°C with a moisture content of 30%. The highest value (68.46%) for resistant starch was achieved at 20% moisture level and 30°C. After eating pudding, blood sugar spiked for the first 60 and 90 min before gradually dropping off over the next 240 min. As a whole, the highest IAUC and TIAUC values, as well as the glycemic index and load, were observed in potato starch heated to 70°C, which contained 40% moisture. Most parameters achieved their highest values when 40% moisture was added and the heat was applied at 70°C.